Chronology for the East GReenland Ice-core Project (EGRIP), extended to 108,305 years before 2000 CE - Sune Olander Rasmussen; Giulia Sinnl (PANGAEA, 2025)
This data file provides the chronology (named GICC05-EGRIP-1) for the deep ice core from the East GReenland Ice-core Project (EGRIP) down to 108,305 years before 2000 CE. We rely mainly on volcanic events and common patterns of peaks in dielectric profiling (DEP), electrical conductivity measurements (ECM) and tephra records for the synchronization between the EGRIP, NEEM and NGRIP ice cores in Greenland. We transfer the annual-layer-counted Greenland Ice Core Chronology 2005 (GICC05) timescale from the NGRIP core to the EGRIP ice core by means of these match points. This data file extends earlier chronologies.